1064 LONG QTC IN HCM: A CONSEQUENCE OF MYOCARDIAL HYPERTROPHY OR A DISTINCT GENETIC DISEASE?. (15th December 2022) - Cava, Francesco; Micolonghi, Caterina; Savio, Camilla; Musumeci, Maria Beatrice; Melato, Giacomo Tini; Petrucci, Simona; Alesi, L; Germani, Aldo; Piane, Maria; Autore, Camillo; Rubattu, Speranza Donatella
Abstract: Hypertrophic cardiomyopathy (HCM) is an autosomal dominant condition, characterized by the presence of unexplained left ventricular hypertrophy. This condition is usually associated with electrocardiographic abnormalities including QTc prolongation reported in the 13% of HCM patients. The main explanation for QTc prolongation in HCM is myocardial hypertrophy and the related structural damage. However, mechanisms other than myocardial hypertrophy, including long QT syndrome (LQTS) gene mutations, may also be involved. The addictive effect of 2 disease-causing mutations has been already reported in other pathological conditions. In the present study we investigated the possible co-inheritance of pathogenic variants associated with both LQTS and HCM, exploring the hypothesis of a distinct genetic basis underlying QTc prolongation in HCM. For this purpose, we considered a cohort of 150 HCM patients carrying pathogenic variants in sarcomeric genes. Out of them we selected 25 patients carrying a QTc prolongation not explained by any other cause (drugs, etc). The QTc was considered prolonged if greater than 450 ms in males and greater than 470 ms in females. NGS analysis was performed with Illumina TrueSight Cardio panel genes on Illumina MiniSeq platform to evaluate the presence of pathogenetic variants in LQTS related genes. We identified pathogenic/likely pathogenic variants in LQTS related gene KCNQ1 (c.1781G>A, p. Arg594Gln; c.532G>A, p. Ala178Thr) in two patients (8%) and uncertain significant variants in SCN5A, KCNJ5, AKAP9 and ANK2 in four patients (16%). Although the results of our study are limited by the small number of patients included in the analysis, they highlight a minor contribution of LQTS genes in HCM patients with a QTc prolongation. The screening for ion channel gene mutations should be considered in HCM patients with QTc prolongation, not explained by any other cause. This strategy may be important for risk stratification and treatment planning.